Risk factors for maxillofacial injuries in a Brazilian emergency hospital sample - LELES, José Luiz Rodrigues (J Appl Oral Sci, 2010)
BACKGROUND: Maxillofacial injuries occur in a significant number of trauma patients. Epidemiological assessments are essential to reaffirm patterns, identify new trends and develop clinical and research priorities for effective treatment and prevention of these injuries. OBJECTIVE: The aim of this study was to identify the epidemiological profile and risk factors associated with maxillofacial trauma treated at a referral emergency hospital for the Public Health System in the State Capital of Goiás, Brazil. MATERIAL AND METHODS: A cross-sectional study was designed including 530 patients with maxillofacial trauma, 76% male, with a mean age of 25.5±15.0 years. Data were collected between May 2003 and August 2004 over weekly shift-working periods. Results: The main causes of trauma were traffic accidents (45.7%) and physical assaults (24.3%), and differences in etiological factors were identified according to gender (p<0.001). The distribution of patients according to age and etiology showed significant differences for traffic accidents (p<0.01), physical assaults (p<0.001), falls (p<0.001) and sport injuries (p<0.01). In the multinomial logistic regression analysis (R(2) = 0.233; p<0.05), age was associated with injury in traffic accidents and falls (p<0.01), sports-related accidents were associated with males (p<0.05), and alcohol consumption with assaults and traffic accidents (p<0.001). Facial soft tissue lesions were found in 98% of patients and facial fractures in 51%. CONCLUSIONS: The significant association of maxillofacial trauma with young males and alcohol consumption reinforces the need for educational strategies and the development of policies for the prevention and reduction of associated damage in this specific risk group.